Decolonisation of curriculum: the case of language education policy in Nepal (UCL Press, 2022)
While decolonisation is usually discussed in relation to countries that were formally colonised, countries that have not been formally colonised have also faced challenges related to colonialism. In this case, it is worth considering whether decolonial theory has more widespread applicability to respond to global challenges faced in the postcolonial era. This article documents the historical trajectories of colonisation and decolonisation of the school curriculum in Nepal. Although Nepal was never formally colonised, the introduction of modern schooling in Nepal was informed by the British colonisation of India, where local languages were replaced by English in the curriculum, diminishing the value of local languages and knowledges. Against this backdrop, the Nepal government issued a series of policies supporting Nepali supremacy, but the expansion of English was not significantly challenged. Rather, the policies resulted in a double colonisation of ethnic/Indigenous languages: external colonisation by English, and internal colonisation by the Nepali language. However, significant decolonisation efforts have recently made space for minoritised languages in the curriculum. This article illustrates these colonisation and decolonisation waves, shaped by the government, local communities and other actors. Drawing on Nepal's legislative and educational policies, the article relates language policy decisions and actions as decolonial efforts to support ethnic/Indigenous languages and explores the implications for understanding tensions around decolonisation of curriculum.